Democratic leadership and employee job satisfaction in Malaysian public sector enforcement agencies - Sahib, Ghazali Shafi Amanullah; Ali, Asiah; Mohd Beta, Raja Mayang Delima (International Journal of Accounting, Finance and Business, 2026)
Job satisfaction is a crucial determinant of employee performance and organizational effectiveness, particularly in public sector and enforcement-related agencies. Leadership style, especially democratic leadership, has been widely recognised as a factor that can enhance employee satisfaction through participation, trust, and shared decision-making. This study examines the relationship between democratic leadership styles and job satisfaction among employees in Agensi Antidadah Kebangsaan (AADK) Port Dickson, Negeri Sembilan. This study employed a quantitative, cross-sectional survey design using simple random sampling. Data were collected from 220 employees through a structured questionnaire adapted from established instruments. Democratic leadership and job satisfaction were measured using five-point Likert scales. Data were analysed using descriptive statistics, normality tests, and Pearson correlation analysis to determine the relationship between the variables. The findings revealed a moderate and statistically significant positive relationship between democratic leadership and job satisfaction (r = 0.447, p < .001). Employees who perceived higher levels of democratic leadership practices reported greater satisfaction with their jobs. Descriptive results also indicated that democratic leadership behaviours such as participative decision-making, respectful feedback, and autonomy were frequently practised within the organisation. The study concludes that democratic leadership plays a significant role in enhancing job satisfaction among AADK employees. Strengthening democratic leadership practices through targeted leadership training and policy support can contribute to a more satisfied, committed, and productive workforce within public sector organisations.